Analysis of genetic factors associated with fatty liver disease‐related hepatocellular carcinoma - Tomomi Kogiso; Yuri Ogasawara; Kentaro Horiuchi; Makiko Taniai; Katsutoshi Tokushige (Cancer Medicine, 2023)
Abstract Aim Single‐nucleotide polymorphisms (SNPs) in PNPLA3 and hydroxysteroid 17‐beta dehydrogenase 13 (HSD17B13) genes are associated with fatty liver disease (FLD) progression and carcinogenesis. In the present study, we evaluated the characteristics of Japanese FLD patients according to HSD17B13 polymorphisms. Methods We enrolled 402 patients who were clinically and pathologically diagnosed with FLD (alcoholic: 63 cases, nonalcoholic: 339 cases) at our hospital in 1990–2018 (228 males; median age: 54.9 [14.6–83.6] years). FLD patients with HSD17B13 A/A (212 cases) and others (A/AA or AA/AA; 190 cases) were compared. Results Compared to patients with HSD17B13 A/A and others, those with the A/A genotype showed increased incidence of hepatocellular carcinoma (HCC) (A/A vs. others; 18.4% vs. 9.5%, p = 0.01), cardiovascular diseases (14.2% vs. 4.2%, p < 0.01), and hypertension (56.6% vs. 47.4%, p = 0.06). In patients without A/A, the HCC incidence was significantly reduced in those with alcohol‐related FLD, fibrosis‐4 index <2.67, and the PNPLA3 CC genotype; however, there was no significant difference in nonalcoholic‐FLD. Patients without HSD17B13 A/A showed severe steatosis (77% vs. 88.6%, p < 0.01). New HCC developed in 11 cases and the 5–year incidence rate of HCC was 3.3% in patients with both PNPLA3 GG/GC and HSD17B13 A/A, which was significantly higher than the rate for those with other SNP profiles (0.6%, p = 0.03). Conclusions Inhibiting HSD17B13 activity may prevent HCC development, particularly in alcohol‐related FLD and low‐risk patients. Therefore, combinations of SNPs and other risk factors can be used for screening FLD–HCC.